Long-term left atrial adaptations to reduced training load in former elite athletes: a long-term follow-up longitudinal observational study - Ahmad Sajadieh; Robin Christensen; Jens Jakob Thune; Mikkel Aaroee; Susanne Glasius Tischer; Christian Have Dall; Hanne Rasmusen (BMJ Open Sport & Exercise Medicine)
Objective Our objective was to evaluate the effects of long-term reduced training on the left atrium (LA) in elite endurance athletes and to elucidate sex-specific differences in LA detraining patterns.Methods In this long-term longitudinal echocardiographic study of 50 active elite endurance athletes a follow-up examination was performed 7 years after retirement from the elite programme. All echocardiographic measurements were indexed for body surface area. We analysed the changes between baseline and follow-up measures using analysis of covariance models adjusted for baseline level, sex and enrolment age as covariates. Results are reported as least squares means with two-sided 95% CIs.Results LA enlargement (left atrial maximum volume index) remained unchanged from baseline (change from baseline: 1.4mL/m2, 95% CI: −0.7 to 3.5 mL/m2) despite significant reductions in VO2max (change from baseline: −864mL/min, 95% CI: −1091 to −637 mL/min). In contrast, left ventricular (LV) end-diastolic volume was reduced (change from baseline: −8mL/m2, 95% CI: −11 to −5 mL/m2), consistent with reduced VO2max. LA contraction strain was increased (change from baseline: 1.4%, 95% CI: 0.4% to 2.5%), while LV filling pressure increased (E/e’ change from baseline: 0.4, 95% CI: 0.1 to 0.7).Conclusions 7 years of reduced training does not reverse exercise-induced LA enlargement in former elite endurance athletes. LA contractile function improved with higher LV filling pressure, suggesting that age-related LV pressure increases may contribute to chronic LA dilation, though irreversible adaptations like fibrosis cannot be ruled out.Trial registration number NCT05555849.